Level of Knowledge “Cerdik” Programs on Blood Pressure in Hypertension Patients - Yulanda, Nita Arisanti; Dika Putri, Uray Weza Azalia; Mita, Mita (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT  Hypertension is one of the leading causes of death. This disease has taken millions of lives and is a covert killer. The rise in hypertension rates is mainly in developing countries such as Indonesia. Indonesia faces 63 million documented cases of hypertension, causing 427,218 deaths each year and ranked third among the ten most common diseases in West Kalimantan, in the city of Pontianak. Bad lifestyle is one of the factors causing hypertension. In order to address the prevalence of hypertension, the Indonesian government has proposed the implementation of CERDIK programmes. However, a gap has been found between the programmes implemented and the trend of increasing prevalence. This study is to find out the relationship of blood pressure of hypertensive patients with the level of knowledge of patients about the CERDIK program at the Clinic of Neurology of RSUD Dr. Soedarso Pontianak. The design of this study was a quantitative writing design that uses cross-sectional methodology. The random sample sampling consisted of 58 respondents, determined using Spearman's rho hypothesis test. Based on the writing findings, the majority of participants (36.2%) belonged to early geriatric demographics (age 46-55), with a female majority (81%). 48.3% of respondents had a high school education or higher, and 34.5% were employed as housewives. The proportion of participants with a satisfactory level of knowledge reached 81% of the total sample. Nearly half of respondents (47%) had normal high blood pressure and grade 1 hypertension. This research suggests that there is no statistically significant correlation between the blood pressure of hypertensive patients and their level of knowledge of the CERDIK program. Keywords: “CERDIK Program”, “Hypertension”, “Knowledge”.